A method of increasing efficiency in the transmission of information in telecommunication networks - Артеменко, В. А.; Богданова, Н. В. (Problems of Informatization and Control, 2008)
A new method for the separation of traffic flows on the boundary node MPLS, which improves the efficiency of information transmission in telecommunication networks